High Pressure Gas Xenon TPCs for Double Beta Decay Searches - Gomez-Cadenas, Juan J.; Monrabal Capilla, Francesc; Ferrario, Paola (Frontiers in Physics, 2019)
This article reviews the application of high pressure gas xenon time projection chambers to neutrinoless double beta decay experiments. First, the fundamentals of the technology and the historical development of the field are discussed. Then, the state of the art is presented, including the prospects for the next generation of experiments with masses in the ton scale.